2022
DOI: 10.11591/ijere.v11i2.22258
|View full text |Cite
|
Sign up to set email alerts
|

The maturity levels of the digital technology competence in vocational education

Abstract: <span>This study aimed to analyze the maturity level of teachers and vocational students. It also measured differences in the maturity level of teachers and vocational students in mastering the digital technology competence (DTC) in vocational education. Quantitative research used a design developed by Hoy and Adams. A total of 233 respondents came from public and private schools in vocational schools in Yogyakarta, Indonesia. Data was collected using a Likert scale questionnaire (1-4). The data were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 32 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…Skills in using technology and supporting equipment are the most important aspects ( Chitkushev et al, 2014 ). Technological skills refer to the basic level to the highest level and depth of digital technology ( Arifin et al, 2020 ; Astuti et al, 2022 ; Mutohhari et al, 2021 ; Sutiman et al, 2022 ). Pavlova (2009) classifies five important skills in using digital technology, namely awareness, literacy, capability, and creativity, and they are critical in using digital technology.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Skills in using technology and supporting equipment are the most important aspects ( Chitkushev et al, 2014 ). Technological skills refer to the basic level to the highest level and depth of digital technology ( Arifin et al, 2020 ; Astuti et al, 2022 ; Mutohhari et al, 2021 ; Sutiman et al, 2022 ). Pavlova (2009) classifies five important skills in using digital technology, namely awareness, literacy, capability, and creativity, and they are critical in using digital technology.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In this case, technological competence in e-learning operations is needed to achieve successful implementation, marked by high student satisfaction in learning to use e-learning. Astuti, Arifin, Nurtanto, Mutohhari, and Warju (2022) and Pavlova (2009) identify five skills that are included in technological competence: technological awareness, technological literacy, technological capability, technological creativity and technological criticism. These five skills have become an important foundation for exploring the benefits of elearning, in line with the results of several past studies showing that the development of digital technology competencies increases students' optimism and ability to manage e-learning (Al-araibi et al, 2019).…”
Section: Effects Of Technological Competencies Motivation and E-learn...mentioning
confidence: 99%
“…During the COVID-19 pandemic, several research reports and review reports agreed on the problem of unpreparedness for e-learning due to a lack of competence in using digital technology to use e-learning systems (Almaiah et al, 2020;Helm, Huber, & Loisinger, 2021;Pokhrel & Chhetri, 2021;Toquero, 2020). The unpreparedness of the students was identified through their low media information, lack of familiarity with learning management systems, lack of understanding of the supporting equipment needed, limited accessibility and a crisis of attitudes and ethics in the use of digital technology (Astuti et al, 2022;Mutohhari, Sutiman, Nurtanto, Kholifah, & Samsudin, 2021;Sutiman, Sofyan, Soenarto, Mutohhari, & Nurtanto, 2022). In line with this, other studies also identified students' lack of experience in using technology and supporting equipment to support e-learning, thus requiring competency development in that direction (Daniel, 2020).…”
Section: Technological Competencies and Motivation For E-learning Rea...mentioning
confidence: 99%
See 1 more Smart Citation
“…Online learning is widely assessed and perceived by various parties as resulting in a decrease in the achievement of learning objectives (Hamid et al, 2022;Prasetyo et al, 2021;Zapata-Cuervo, Montes-Guerra, Shin, Jeong & Cho, 2022). However, over time, various virtual face-to-face learning innovations have been discovered to overcome the problem of unsatisfactory learning achievements and some of these methods have proven to be effective (Arifin, Nurtanto, Warju, Rabiman & Kholifah, 2020;Astuti, Arifin, Nurtanto, Mutohhari & Warju, 2022;Bahasoan, Ayuandiani, Mukhram & Rahmat, 2020;Nurtanto, Kholifah, Masek, Sudira & Samsudin, 2021). However, as the spread of COVID-19 slowed down, the virtual face-to-face learning policy which had been practiced for about a year and a half began to shift back to the face-to-face mode again (Hanafi et al, 2021;Pacheco, 2021).…”
Section: Introductionmentioning
confidence: 99%